Ukamenia Oku, 1981 (Lepidoptera: Tortricidae: Olethreutinae), new record for Thailand with descriptions of a new species - Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2020)
The genus Ukamenia Oku, 1981 is recorded the first time for Thailand and a new species, Ukamenia thailandica n. sp., is described. Photograph of living specimens of U. thailandica n. sp. in natural resting posture is present. The one new taxon increases the number of described Ukamenia species to 4.